Reliability of a Newly Developed Tool to Assess and Classify Work-related Stress (TAWS-16) for Indian Workforce - Gautham Melur Sukumar; Runalika Roy; Mariamma Philip; Gururaj Gopalkrishna (Korean Society for Preventive Medicine, 2023)
Objectives Work stress is associated with non-communicable diseases, increased healthcare costs, and decreased work productivity among employees in the information technology sector. There is a need for regular work-stress screening among employees using valid and reliable tools. The Tool to Assess and Classify Work Stress (TAWS-16) was developed to overcome limitations in existing stress assessment tools in India. This study aimed to test the reliability of TAWS-16 in a sample of managerial-supervisory employees. Methods This observational reliability study included data from 62 employees. Test-retest and inter-method reliability were investigated using a TAWS-16 web application and interview by telephone, respectively. Kappa values and intra-class correlation coefficients were calculated. Internal consistency was assessed through Cronbach's alpha. Results For both test-retest and inter-method reliability, the agreement for both work-related factors and symptoms suggestive of work stress exceeded 80%, and all kappa values were 0.40 or higher. Cronbach's alpha for test-retest and inter-method reliability was 0.983 and 0.941, respectively. Conclusions TAWS-16 demonstrated acceptable reliability. It measured stressors, coping abilities, and psychosomatic symptoms associated with work stress. We recommend using TAWS-16 to holistically identify work stress among employees during periodical health check-ups in India.